Diagnostic Profiles: A Standard Setting Method for Use With a Cognitive Diagnostic Model. Issue 4 (1st December 2016) - Skaggs, Gary; Hein, Serge F.; Wilkins, Jesse L. M.
Abstract : This article introduces the Diagnostic Profiles (DP) standard setting method for setting a performance standard on a test developed from a cognitive diagnostic model (CDM), the outcome of which is a profile of mastered and not‐mastered skills or attributes rather than a single test score. In the DP method, the key judgment task for panelists is a decision on whether or not individual cognitive skill profiles meet the performance standard. A randomized experiment was carried out in which secondary mathematics teachers were randomly assigned to either the DP method or the modified Angoff method. The standard setting methods were applied to a test of student readiness to enter high school algebra (Algebra I). While the DP profile judgments were perceived to be more difficult than the Angoff item judgments, there was a high degree of agreement among the panelists for most of the profiles. In order to compare the methods, cut scores were generated from the DP method. The results of the DP group were comparable to the Angoff group, with less cut score variability in the DP group. The DP method shows promise for testing situations in which diagnostic information is needed about examinees and where that information needs to be linked to a performance standard.